Evaluation of the effect of inadaptable risk factors & social status on Diabetic Foot Ulcer - Khalique, Saniya (International Journal of Endorsing Health Science Research, 2014)
Diabetic Foot Ulcer subjects (DFUS) were clinically examined in the urban areas of Karachi. Neuropathy, peripheral vascular disease, foot deformity, improperly fitted shoes can make a diabetic person at risk of foot ulcer. In the present study, prevalence, role of inadaptable risk factors (age, gender, height) and socio-economic status were examined in DFUS and normal diabetic patients (NDP) taken as control. A total of randomly selected subjects N= 59; male=33, female=26 (DFUS: n=41; male=22, female=19; NDP: n=18; male=11, female=7). In this study prevalence of DFU was found in male gender as 54% of our patients were male and 46% were female. Mean ± S.E.M. of male DFUS height was 5.7 ± 0.353 ft while that of women was 5 ± 0.306 ft, this greater height in male makes them predominant for DFU. Mean ± S.E.M. of age for DFUS males: 58 ± 10.237 years, that is comparatively higher than control NDP males: 56.81 ± 10.235 years. Mean ± S.E.M. of age for DFUS females: 54 ± 11.18 years which is also significantly higher than control NDP females: 49.57 ± 9.727 years. The greater part of the investigated patients belonged to lower class (54% males & 74% of females).